KUALITAS PELAYANAN IBADAH HAJI DI KEMENTERIAN AGAMA KOTA PONTIANAK - Nurul Dini Radiyah E.21109050 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Quality Service at the Ministry of Religious Affairs Hajj Pontianak, includes three aspects studied, including: (a). Attitudes and behavior of workers in providing services. (b). Factors inhibiting the Ministry of Religious Affairs in providing good service to pilgrims. (c). Efforts made the Ministry of Religious Affairs in improving the quality of service to pilgrims. This study uses the analytical descriptive method with the qualitative technique in the data processing. As for the informants in this study were the parties involved in the service of pilgrims and those who receive those services within the scope of the Office of Religious Pontianak. The research found that the attitudes and behavior of workers in providing services is a courtesy and on time. While the officers were the limiting factor in providing services to pilgrims, including: (a). The lack of computer tools that contribute to hamper the smooth pilgrimage services in the registration section, and (b). Network or system to access services for Hajj departure information on line using the application Haji Integrated Computerized System (SISKOHAT) often jammed or error so that the transaction can not run smoothly. The efforts that have been carried out by the Ministry of Religious Affairs in improving the quality of care is to provide direction guidance relating to the use of computer-related skills with SISKOHAT for faster, timely and thorough in providing services topilgrims. In addition, the Ministry of Religious Affairs has also sought to improve the quality of services to Haj pilgrims, among others, by providing information about registration procedures pilgrimage services, and the provision of facilities and infrastructure. Keywords : Quality of Hajj Service, Behavioral Services Officer, Obstacles of Services Quality, and Effort Service Officers.